Free will, agency, and meaning in life - Pereboom, Derk 1957- (Oxford University Press, 2014)
Derk Pereboom articulates and defends an original, forward-looking conception of moral responsibility. He argues that although we may not possess the kind of free will that is normally considered necessary for moral responsibility, this does not jeopardize our sense of ourselves as agents, or a robust sense of achievement and meaning in life